English Learning Motivation and Achievement of Police Students in Ho Chi Minh City from a Sociocultural Perspective - Hoa, Lê Hương (VNU Journal of Foreign Studies; Vol 31 No 1, 2015)
Among  the  factors  influencing  students’  studies,  motivation  is considered  to  be one of the most important factors for different achievement levels. The purposes of this study were (i) to find out the students' levels of motivation to study English, (ii) to identify the sociocultural factors influencing that motivation and (iii) to investigate the relationship between students' motivation and their achievement. The subjects were 509 first-year students at the People’s Police University (PPU). The instruments used for data collection were questionnaires and focus group interviews. The data from the returned questionnaires was statistically analyzed using the SPSS program to derive percentages, frequencies, means, standard deviations, as well as to perform exploratory factor analysis and multiple linear regression. Findings from this study indicated that the majority of the students were motivated and had a positive attitude toward learning English; however, their reasons for learning English were utilitarian as a means to an end such as to pass the exams rather than for pleasure or, simply, to broaden their knowledge. Students' motivation and their English learning achievement were strongly and positively correlated with each other (p=.000<.05). If we want to improve achievement, we should influence motivation, especially with regard to two of the most important motivational factors: learning situational components and group cohesion. The findings could be useful for researchers and teachers in improving students’ achievement by devising effective teaching and learning strategies to increase students’ motivation. Keywords: Students’ motivation, academic achievement, socio-cultural perspective.